Les débuts de la poste à Ahunstic-Cartierville - Poitras, Jean (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Bordeaux; Cartierville; Poste; Sault-au-Récollet

Between the Future and the Present: Montreal University Student Youth and the Post-War Years, 1945-1960 - Hébert, Karine (Cultures of Citizenship in Post-War Canada, 1940-1955, 2003)
Keywords: Université McGill; Université de Montréal; Étudiants

Historique du bureau postal de Montréal (1763-2012) - Nolet, Jacques (Collection du bicentenaire, 2012)
Keywords: Poste

Urban Occupations Urbaines: Curating the Post-industrial Landscape - Janssen, Shauna (Université Concordia, 2014)
Keywords: Gentrification; Griffintown; Lachine (canal); Patrimoine; Quartiers

Communalisations ethniques post-migratoires: le cas des Turcs de Montréal - Bilge, Sirma (Université Sorbonne Nouvelle - Paris 3, 2002)
Keywords: Turcs

Photogenic Montreal: Activisms and Archives in a Post-Industrial City - Langford, Martha; Sloan, Johanne (McGill-Queen's / Beaverbrook Canadian Foundation Studies in Art History Series, 2021)
Keywords: Conservation; Patrimoine; Photographie; Quartiers

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens

Leonardo da Montreal: The Rhetoric of Italianità and the Canadian Post-Nation - Fratiloiu, Raluca Maria (Université Concordia, 2006)
Keywords: Centre Leonardo Da Vinci; Italiens

Les immigrants roumains post-1989: vers une nouvelle communauté ethnoculturelle montréalaise? - Busuioc, Iulian (Université du Québec à Montréal, 2007)
Keywords: Roumains

Organized Righteousness Against Organized Viciousness: Constructing Prostitution in Post World War I Montreal - Herland, Karen (Université McGill, 2005)
Keywords: Prostitution

Poverty and Wealth in the Post-War Montreal Area: A Landscape in Motion - Séguin, Anne-Marie; Negron, Paula; Apparicio, Philippe (Montreal: The History of A North American City, 2018)
Keywords: Gentrification; Pauvreté; Quartiers

Le genre d’une migration post-coloniale: de Meknès (Maroc) à Montréal (Québec) - Cohen, Yolande (Genre et Histoire, 2010)
Keywords: Femmes; Féminisme; Historiens; Juifs; Marocains

Citystats and the History of Community and Segregation in Post-Second World War Urban Canada - Stanger-Ross, Jordan (Journal of Canadian Historical Association / Revue de la Société historique du Canada, 2008)
Keywords: Autochtones; Juifs

Made in Montreal: A Study of Geography and Priorities of Small Urban Manufacturers in Post-Industrial Montreal - Carruthers, Alex (Université McGill, 2012)

Disputed Post-Industrial Landscapes: An Enquiry into the "Loft-Living" Cultural Model in Montréal's Saint-Henri - Tam, Edith (Université Concordia, 2009)
Keywords: Logement; Quartiers; Saint-Henri

Analyse des références de la presse écrite aux nationalismes canadien et québécois dans le contexte post-référendaire québécois - Pinard-Dostie, Marilaine (Université de Sherbrooke, 2015)
Keywords: Devoir (Le); Journal de Montréal (Le); Nationalisme; Presse (La); Référendums

L'histoire avant et après de Queen of Angels Academy/The pre and post history of Queen of Angels Academy - Nieuwendyk, Dick (Héritage Dorval, 2021)
Keywords: Royal Montreal Golf Club

L'histoire et la mémoire en suspens: le patrimoine des villes post-industrielles et le cas du silo no 5 de Montréal - Martineau, Marie-Nathalie (Université du Québec à Montréal, 2010)
Keywords: Patrimoine

Apologie de l'indulgence plénière dans l'Église post-tridentine: le De iubilaeo, sive indulgentiis, et plenaria remissione de Laurentius Nagelmaker (1576) - Le Brun-Gouanvic, Claire (Ouvrages phares de la Réforme & de la Contre-Réforme dans les collections montréalaises, 2014)

Urban governance after urban renewal: The legacies of renewal and the logics of neighbourhood action in post-renewal Little Burgundy (1979 – 1995) - Goyette, Kiley (Université Concordia, 2017)
Keywords: Gentrification; Groupes populaires; Logement; Petite-Bourgogne; Quartiers

De fiel et de miel: les représentations de la stratégie de gestion de la crise post-référendaire présentes dans la presse canadienne, 1995-1999 - Lapointe Gagnon, Valérie (Université Laval, 2008)
Keywords: Anglophones; Francophones; Nationalisme; Référendums

Reading the Multimedia Archive Surrounding Montreal's Post-War LGBTQ Bars: A Genealogical Return to Madame Arthur and Il était une fois dans l'Est - Pidduck, Julianne (Quebec Studies, 2015)
Keywords: Alcool

Les réseaux des «lyriques» et des «veillées»: une histoire de la chanson au Québec dans l'entre-deux-guerres par la radiodiffusion au poste CKAC de Montréal (1922-1939) - Bellemare, Luc (Université Laval, 2012)
Keywords: CKAC; Chanson; Radio

Institutions de Verdun 2 (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2007)
Keywords: Côte-Saint-Paul; Hôpital Douglas; Hôpitaux psychiatriques; Poste; Quartiers; Verdun

We Admire Modern Parents. The École des Parents du Québec and the Postwar Québec Family, 1940-1949 - Baillargeon, Denyse (Cultures of Citizenship in Post-War Canada, 1940-1955, 2003)
Keywords: Famille

The Pastness of Allô Police - Straw, Will (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Criminalité; Photographie

Erase and See: The Photogénie of a Metropolis in Progress - Langford, Martha (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Paysages; Photographie

Architecture, Photography, and Power: Picturing Montreal, 1973-74 - Imogen Hammond, Cynthia (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Conservation; McConnell, John Wilson; McConnell, John Wilson (maison); Patrimoine; Photographie; Shaughnessy (maison); Van Horne (maison); Van Horne, William

Through the Lens of Edith Mather: Photographing Demolition and the Transforming City - Southcott, Tanya (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Conservation; Femmes; Patrimoine; Photographie; Rues

A Heuristic Archive: Jean-Paul Gill's Red Light Photographs - Guillaume, Philippe (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Archives; Patrimoine; Photographie; Quartiers; Saint-Laurent (quartier)

Re-activations: Alain Chagnon’s Plateau-Mont-Royal in Translation - Langford, Martha (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Photographie; Plateau Mont-Royal; Quartiers

Emmanuel Persillier-Lachapelle. Un précurseur de la santé publique (1845-1918) - Gaumer, Benoît; Desrosiers, Georges (Les Presses de l'Université Laval, 2019)
"Le nom d'Emmanuel Persillier-Lachapelle est bien connu des Qu??b??coises et des Qu??b??cois engag??s dans le domaine de la sant?? publique. Un prix portant son nom est d??cern?? chaque ann??e par le minist??re de la Sant?? et des Services sociaux du Qu??bec ?? ceux ou celles, personne ou organisation, qui travaillent dans ce domaine, dont il fut l'un des pr??curseurs ?? la fin du XIXe si??cle et au d??but du XXe. Homme d'action au savoir-faire ??clectique, il a occup?? de nombreux postes de responsabilit?? dans ce qui est devenu le syst??me de sant?? et des services sociaux du Qu??bec. Premier pr??sident et fondateur du Conseil d'hygi??ne de la province de Qu??bec, anc??tre de ce dernier, il a ??t?? en m??me temps cofondateur et administrateur de l'H??pital Notre-Dame ?? Montr??al. Dipl??m?? de l'??cole de m??decine et de chirurgie de Montr??al, c'est dans celle-ci qu'il entreprit d'abord sa carri??re de professeur de m??decine, avant de passer ?? l'annexe de la Facult?? de m??decine de l'Universit?? Laval ?? Montr??al, devenant le doyen lorsque les deux ??coles ont ??t?? r??unies. Tr??s engag?? dans l'organisation de la profession m??dicale, il a longtemps occup?? le poste de pr??sident du Coll??ge des m??decins et chirurgiens de la province de Qu??bec. Lib??ral en politique, bien qu'en r??serve de celle-ci, il a ??t?? l'un des quatre commissaires de la Ville de Montr??al lors de la mise en tutelle de cette derni??re par le gouvernement provincial. N?? ?? Sault-au-R??collet en 1845, sa principale oeuvre demeura cependant la cr??ation du Conseil d'hygi??ne de la province de Qu??bec, occupant le poste de pr??sident jusqu'?? sa mort en 1918. "Habile administrateur, philanthrope ??prouv??, ??conomiste distingu??, diplomate consomm??, d'un jugement absolument s??r, d'une int??grit?? ?? toute ??preuve", il a m??rit?? ainsi ces ??loges de ses pairs francophones et anglophones de l'??poque, demeurant un mod??le pour les nouveaux experts de la sant?? publique au XXIe si??cle."--
Keywords: Hôpital Notre-Dame; Hôpitaux; Hôtel-Dieu; Médecine; Tuberculose; École de médecine

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail